"OSTEOCHONDROSIS OF THE SPINE": LOSSES AND HOPES - Константин Борисович Петров; Татьяна Векентьевна Митичкина; Наталья Анатольевна Ивонина; Сергей Николаевич Филимонов (Медицина в Кузбассе)
The article is devoted to a long-term discussion of the nosological and terminological essence of such a clinical and morphological phenomenon as osteochondrosis of the spine. Objective – to study the attitude of the medical community to the etiopathogenetic role of dystrophic changes in the spinal motion segments with damage to the musculoskeletal system over the past 10 years. Results. Over the past decade, a steady trend has emerged in the world to recognize the connection between pathomorphological changes in the spine and «back pain», there has been a boom in scientific publications on this topic. Conclusions. There is a gradual rehabilitation of the theory of osteochondrosis of the spine developed in the USSR, but the term «osteochondrosis» is unlikely to be revived again.